Glutathione: Pharmacological aspects and implications for clinical use in non-alcoholic fatty liver disease - Santacroce, Giovanni; Gentile, Antonella; Soriano, Simone; Novelli, Andrea; Lenti, Marco Vincenzo; Di Sabatino, Antonio (Frontiers in Medicine, 2023)
Glutathione is a tripeptide synthesized at cytosolic level, that exists in cells in a reduced form (thiol-reduced-GSH-) and in an oxidized form (disulfide-oxidized). The antioxidant function of GSH has led to speculation about its therapeutic role in numerous chronic diseases characterized by altered redox balance and reduced GSH levels, including, for instance, neurodegenerative disorders, cancer, and chronic liver diseases. Among these latter, non-alcoholic fatty liver disease (NAFLD), characterized by lipid accumulation in hepatocytes, in the absence of alcohol abuse or other steatogenic factors, is one of the most prevalent. The umbrella term NAFLD includes the pure liver fat accumulation, the so-called hepatic steatosis or non-alcoholic fatty liver, and the progressive form with inflammation, also known as non-alcoholic steatohepatitis, which is related to the increase in oxidative stress and reactive oxygen species, eventually leading to liver fibrosis. Although the pathogenetic role of oxidative stress in these diseases is well established, there is still limited evidence on the therapeutic role of GSH in such conditions. Hence, the aim of this review is to depict the current molecular and pharmacological knowledge on glutathione, focusing on the available studies related to its therapeutic activity in NAFLD.